Intellectual disability in Indigenous Australians: issues and challenges. (December 2015) - Balaratnasingam, Sivasankaran; Roy, Meera
Objectives: Literature on Indigenous Australians (Aboriginal and Torres Strait Islander people) and intellectual disability (ID) is summarized in order to identify current state of knowledge, gaps, and areas for further research. Methods: A selective review of psychiatric literature using relevant medical databases was undertaken. Key articles were identified and their findings described. Results: ID is reported to be more prevalent in Indigenous Australians. Sociocultural constructs and a lack of validated psychometric measures affect what is considered to be ID in Indigenous communities. Prenatal, perinatal, and postnatal factors impair brain development and contribute to ID in Indigenous communities. Comorbid physical and psychiatric disorders need to be assessed and managed. Conclusions: ID is an emerging area of health concern for general and mental health professionals working with Indigenous Australians. This important area requires further research, appropriate training, and resourcing.